Smoking, Cardiac Symptoms, and an Emergency Care Visit: A Mixed Methods Exploration of Cognitive and Emotional Reactions - Tappe, Karyn A.; Boudreaux, Edwin D.; Bock, Beth; O'Hea, Erin; Baumann, Brigitte M.; Hollenberg, Steven M.; Becker, Bruce; Chapman, Gretchen B. (Emergency Medicine International, 2012)
Emergency departments and hospitals are being urged to implement onsite interventions to promote smoking cessation, yet little is known about the theoretical underpinnings of behavior change after a healthcare visit. This observational pilot study evaluated three factors that may predict smoking cessation after an acute health emergency: perceived illness severity, event-related emotions, and causal attribution. Fifty smokers who presented to a hospital because of suspected cardiac symptoms were interviewed, either in the emergency department (ED) or, for those who were admitted, on the cardiac inpatient units. Their data were analyzed using both qualitative and quantitative methodologies to capture the individual, first-hand experience and to evaluate trends over the illness chronology. Reported perceptions of the event during semistructured interview varied widely and related to the individual’s intentions regarding smoking cessation. No significant differences were found between those interviewed in the ED versus the inpatient unit. Although the typical profile was characterized by a peak in perceived illness severity and negative emotions at the time the patient presented in the ED, considerable pattern variation occurred. Our results suggest that future studies of event-related perceptions and emotional reactions should consider using multi-item and multidimensional assessment methods rated serially over the event chronology.